MEMBANGUN SISTEM PENDIDIKAN DEMOKRATIS - Mulyadi, Dr. (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2004)
The paradigm of education in the future is democracy. The system of education, which is democratic will result the alumnus that have influence in the social life and can be involved in making public decisions. However, the reality is not as expected. The system of education, which apply now is education dominated by system of delivering information not processing information. Beside that, the relation between teacher and student is not based on togetherness but domination; the teacher dominates students. Therefore, to develop the democratic education, it is a must to do reformation and reorientation to the system of education. It involves, at least, four aspects: 1. Change the management of education from centralistic to decentralization, 2. Change the curriculum of education from theoretic oriented to problem oriented; how the teacher deliver subject of teaching from the real problem faced by students with constructivist approach. 3. Considering students as subject, not only as object. 4. Teacher does not dominate, but plays as facilitator and motivator (Tut wuri handayani). Keywords: Education and democracy.